Using the ‘Arts’ to Teach Indigenous Australian Studies in Higher Education - Vaughan, Karen (The Australian Journal of Indigenous Education, 2005)
Abstract This paper will discuss some personal philosophies and rationales in approaching and delivering Indigenous Australian studies – approaches that have been influenced and informed by experienced and knowledgeable educators both Indigenous and non-Indigenous. It doesn’t aim or pretend to be unique or innovative in its arguments or approach; instead, it is a reflection on the pathway taken by one Indigenous educator and the thinking behind this – at least at this point in time. As such, it adopts a philosophy that “it’s important to know where we’ve come from in order to make sense of where we are and where we might be heading”. It is hoped that through this reflection and by offering an example of how art (as performance/role-play) has been used in one of my teaching sessions that I might make more sense of my personal practice and contribute in some small way to the important and ongoing debates surrounding teaching Indigenous Australian studies.